Integration of biocoal in distributed energy systems: A potential case study in the Spanish coal-mining regions. (15th January 2023) - Paredes, B.M.; Paredes, J.P.; García, R.
Abstract: Energy has an essential role in socio-economic development, particularly in European coal-mining regions undergoing a transition process which implies searching for alternative fuels to coal. Forestry wastes provide a large amount of biomass that has the potential to be transformed into biocoal to produce solid biofuels. The present work aims to analyse the feasibility of integrating biocoals as a renewable solid fuel, produced by torrefaction and further mechanical densification, in the currently existing coal-consuming facilities. The methodology proposed evaluates existing forest waste resources and their potential conversion into biocoal pellets for use in thermal and electrical energy production. An analysis of the results indicates a potential overall production of 280 kt/year of torrefied pellets in the seven coal-mining regions in Spain evaluated in the study, with the potential to produce 78 MWe or 470 MWth, respectively, and avoid 582 kt/year of CO2 emissions. The average cost for torrefied pellets production would be 148 €/t and require an emission cost of approximately above 45 €/tCO2 to be cost-competitive with coal for direct use in currently existing energy systems. The use of biocoal is shown from resource to energy management for energy conversion systems in the pathway of the energy transition. Highlights: European coal regions must meet EU targets in renewable energy production. Bioenergy from torrefaction is a promising source in the energy transition. Biocoal would avoid 582 kt/year of equivalent CO2 emissions in Spain. New energy conversion strategies can further develop the bioenergy sector.